Zero-set spaces and Pseudocompactness - Gilmour, Christopher (Department of Mathematics and Applied Mathematics, 2023)
We are concerned in this thesis with the intrinsic properties of zero-set spaces and their relationship to other topological-type structures. Our definition of a z-space coincides with that of Gordon's zero set space without the point separation axiom. It is of interest that C:a11fell also omits this axiom.